Application of hybrid algorithms in an optimal allocation model of water and land resources - Wei, Cong; Cheng, Jilin; Jiang, Yushan (Journal of hydroinformatics, 2023)
Ensuring an optimal irrigation system and planting layout for crops in areas with water resource deficiencies is a complex process. A model of the optimal allocation of water and land resources for the irrigation system of the ‘reservoir and pumping station’ under crop rotation was established in this study. For the above complex nonlinear model, two-hybrid algorithms are proposed: (1) the decomposition aggregation dynamic programming (DADP) method and linear programming (LP) successive approximation algorithm [(DADP–LP)SA] and (2) the DADP algorithm based on the orthogonal design (OD) method (OD–DADP). The (DADP–LP)SA and OD–DADP algorithms were compared with the real-coded genetic algorithm (RGA) and particle swarm optimization (PSO) to analyze the performance of the four algorithms. The developed algorithms were applied to the Gao'a irrigation area in the north of Jiangsu Province, China. The solution results showed that the annual output value of water-deficient irrigation areas was improved, and limited water and land resources were optimally allocated, demonstrating the feasibility of the two-hybrid algorithm. Moreover, through a comparative analysis of the optimality and applicability of the four algorithms, it can be observed that (DADP–LP)SA and OD–DADP are more suitable for optimizing the allocation of scarce water and land resources than RGA and PSO.